2019
DOI: 10.3892/ol.2019.10389
|View full text |Cite
|
Sign up to set email alerts
|

HTLV‑1‑associated genes as potential biomarkers for endometrial cancer

Abstract: Endometrial carcinoma (EC) is a malignant neoplasm of the endometrial epithelium, which may be diagnosed by pathological investigations. The aim of the current study was to identify new markers for the diagnosis of EC using machine learning. The association between human T cell lymphotropic virus type 1 (HTLV-1) infection and endometrial cancer risk have not been widely reported. It remains ambiguous whether HTLV-1 infection is associated with several types of cancer. The present study investigated the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Our previous work on HTLV-1/2 epidemiology in northern Brazil demonstrated virus circulation in both healthy and cancer patients of different ethnicities, including Amazonian Amerinds, even though our initial collaborative research work, in early years of 1985, with Maruyama's laboratory in Japan, did not distinguish HTLV-1 from HTLV-2 [67][68][69], but later on, we were aware that HTLV-2 was responsible for the high prevalence among Amazonia Amerinds, except our findings of HTLV-1 positivity among Waiãpi amerinds inhabiting forest areas in the border of the Brazilian Amapa state and French Guyana [70]. Cervix uterine cancer patients exhibited relatively elevated HTLV-1 prevalence [67,69], but scarce data confirmed our results, as published by Du et al [71] assessing the potential association of HTLV-1 to endometrial carcinoma; in the Yucatan peninsula, Góngorra-Bianchi et al [72] showed that Mexican Mayan descendants with high incidence of cervix uterine cancer, yielded HTLV-2 positivity, in both cancer and healthy women, as expected; as well, in Japan and Jamaica, HTLV-1 markers were detected among cervix uterine cancer patients [73,74]. HTLV-1/2 etiological involvement in cervix uterine cancer is elusive despite its high statistical probability.…”
Section: Discussionsupporting
confidence: 79%
“…Our previous work on HTLV-1/2 epidemiology in northern Brazil demonstrated virus circulation in both healthy and cancer patients of different ethnicities, including Amazonian Amerinds, even though our initial collaborative research work, in early years of 1985, with Maruyama's laboratory in Japan, did not distinguish HTLV-1 from HTLV-2 [67][68][69], but later on, we were aware that HTLV-2 was responsible for the high prevalence among Amazonia Amerinds, except our findings of HTLV-1 positivity among Waiãpi amerinds inhabiting forest areas in the border of the Brazilian Amapa state and French Guyana [70]. Cervix uterine cancer patients exhibited relatively elevated HTLV-1 prevalence [67,69], but scarce data confirmed our results, as published by Du et al [71] assessing the potential association of HTLV-1 to endometrial carcinoma; in the Yucatan peninsula, Góngorra-Bianchi et al [72] showed that Mexican Mayan descendants with high incidence of cervix uterine cancer, yielded HTLV-2 positivity, in both cancer and healthy women, as expected; as well, in Japan and Jamaica, HTLV-1 markers were detected among cervix uterine cancer patients [73,74]. HTLV-1/2 etiological involvement in cervix uterine cancer is elusive despite its high statistical probability.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, our study determined that patients with either HTLV-1 or HTLV-2 infection and a cancer diagnosis had worse OS than patients with cancer alone. Studies of PLHTLV have implicated HTLV-1 in various cancers and its promotion of cancer progression ( Arisawa et al, 2003 ; Stienlauf et al, 2013 ; Dias et al, 2018 ; Du et al, 2019 ). Indeed, our findings are consistent with recent retrospective cohort data from Valcarcel et al showing that PLHTLV with concomitant non-ATL cancer diagnoses, excluding diffuse large B-cell lymphoma (DLBCL), had worse survival outcomes than those reported in the general Latin American population ( Valcarcel et al, 2022 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with these two methods, the specificity decreased slightly, but the diagnostic sensitivity can be greatly improved. The prognosis was good for those who were diagnosed with early stage EC, with a 5-year survival rate higher than 90% ( 7 9 ), but most of EC patients were detected at medium or advanced stages of the cancer, who often with lymph node or distant metastasis; the prognosis was poor, who may lose the opportunity of surgical therapy ( 42 ). For these patients with recurrent or metastatic disease, the median overall survival (OS) remained short, with 5-year overall survival rates as low as 16% ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%